2019
DOI: 10.1016/j.athoracsur.2018.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Exposure to Suspect Neurotoxicants From Medical Devices in Newborns With Congenital Heart Defects

Abstract: There is considerable perioperative exposure to DEHP and BPA for neonates undergoing cardiac surgery. For both BPA and DEHP metabolites, infant concentrations were significantly higher than maternal concentrations, consistent with infant's exposure to medical devices. Further study is needed to determine the potential role of these suspect neurotoxicants in the etiology of neurodevelopmental disability after cardiac surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 32 publications
1
29
0
Order By: Relevance
“…However, a recent study carried out specifically in newborns in cardiac surgery showed that extracoporeal circulation medical devices remain highly exposed to DEHP. Indeed, Gaynor et al (2019) [41] demonstrated that the level of 5-OH-MEHP passes from 0.01 µg/mL to 0.229 µg/mL after cardiopulmonary bypass. Our study showed that MEHP had partial agonist effects in the T-screen bioassay, suggesting an action on TRs at concentrations of 10 µg/mL to 20 µg/mL.…”
Section: In Vitro Data Versus Biomonitoring Valuesmentioning
confidence: 99%
“…However, a recent study carried out specifically in newborns in cardiac surgery showed that extracoporeal circulation medical devices remain highly exposed to DEHP. Indeed, Gaynor et al (2019) [41] demonstrated that the level of 5-OH-MEHP passes from 0.01 µg/mL to 0.229 µg/mL after cardiopulmonary bypass. Our study showed that MEHP had partial agonist effects in the T-screen bioassay, suggesting an action on TRs at concentrations of 10 µg/mL to 20 µg/mL.…”
Section: In Vitro Data Versus Biomonitoring Valuesmentioning
confidence: 99%
“…While environmental exposure to BPA is continuous at a relatively low dose (Koch & Calafat, 2009; Vandenberg et al, 2007, 2010)—clinical (Calafat et al, 2009; Duty et al, 2013; Gaynor et al, 2018) and occupational (C. J. Hines et al, 2018; Ribeiro, Ladeira, & Viegas, 2017) environments can result in higher BPA exposures (Table 1) (Calafat et al, 2009; Duty et al, 2013; Gaynor et al, 2018; Huygh et al, 2015). BPA has been detected in 60% of neonatal intensive care unit (ICU) supplies, and experimental studies have identified estrogenic activity in >25% of extracts from these items (Iribarne‐Durán et al, 2019).…”
Section: Bisphenol‐amentioning
confidence: 99%
“…In the final product, DEHP can contribute up to 40% of the finished weight of plastic medical products (e.g., intravenous fluid bags, blood storage bags), and up to 80% of the weight of flexible medical tubing (Halden, 2010; Jaeger & Rubin, 1973, 2010; Plonait, Nau, Maier, Wittfoht, & Obladen, 1993). Since phthalates are not covalently bound to PVC, these chemical additives are known to leach or migrate into surrounding solutions, including blood (Table 2) (Barry et al, 1989; D'Alessandro et al, 2019; Demirel et al, 2016; Gaynor et al, 2018; Green et al, 2005; Kaestner et al, 2020; Karle et al, 1997; Mallow & Fox, 2014; Münch et al, 2020; Peck et al, 1979; Rael et al, 2009; Sjöberg, Bondesson, Sedin, & Gustafsson, 1985; Sjoberg et al, 1985; Stroustrup et al, 2018; Su et al, 2012; Takatori et al, 2008; van der Meer et al, 2014). Moreover, DEHP leaching is exacerbated under conditions of prolonged use, mechanical stress, higher temperature and/or in the presence of lipid‐containing fluids.…”
Section: Di‐2‐ethylhexyl Phthalatementioning
confidence: 99%
“…Phthalate exposures increase after neonatal cardiac surgical treatment, 37 and gestational exposures in the general population have been associated with neurodevelopmental outcomes in children. [38][39][40][41][42]…”
Section: Limitationsmentioning
confidence: 99%